Performance enhancement of triboelectric nanogenerator through hole and electron blocking layers-based interfacial design. (April 2021) - Firdous, Irum; Fahim, Muhammad; Daoud, Walid A.
Abstract: Enhancing negative charge retention sites on a contact surface is a key parameter to boost the performance of triboelectric nanogenerators. However, the unstable positive charge on the other contact surface can also be transferred as all surfaces have both charge donating and accepting regions. To prevent alternate charge transfer and charge recombination, PVDF is doped with phytate ion cluster as the tribopositive layer to trap positive charges through the formation of 18 hydrogen bonds or chelation through mono, di and trivalent cations of the 12 reactive phosphate groups, resulting in a 9.3-fold increase in current density. Moreover, the tribonegative layer is optimized with deeper trap states and more localization of negative charge (i.e . PDMS), which keeps tribocharges for longer duration of 5.5 h and results in a further 32-fold increase in current density to 4.4 mA m −2 . With the intrinsic charge trap enhancement, the device possesses high mechanical stability and durability, where the output performance remains intact after 16 month storage, due to the excellent compatibility of PVDF with phytate. Moreover, when four units of the device are stacked in parallel alternate layered form, an increase in output current from 1.1 µA to 20.9 µA with power density 0.80 W m −2 was obtained, displaying potential of the device design for powering high demand wearable electronics. Graphical Abstract: A 33-fold enhancement in current density is achieved by suppressing interfacial alternate charge transfer and charge recombination through electron blocking in tribonegative layer and hole blocking in tribopositive, resulting in fast charge accumulation rate of 0.330 nC min −1 and a prolonged charge decay time of 5.5 h. ga1 Highlights: Phytate ions with 18 hydrogen bonding and 12 reactive centers for trapping mono, bi and trivalent cation are doped in PVDF. A TENG design with hole and electron trapping layers is developed for the first time to prevent alternate charge transfer. The layers can be charged at faster rate of 0.33 nC min −1 and maintain tribo-charges for longer duration of 5.5 h. The charge density increases from 3.7 to 30 µC m −2 resulting in 32-fold increase in current density, reaching 4.44 mA m −2 . By stacking 4 devices, the current increases to 20.9 µA, showing potential for supporting high power electronics.